Removal of benzidine from polluted water by soluble and immobilized peroxidase in batch processes and continuous horizontal bed reactor - Karim, Zoheb (Environmental technology, 2011)
Bitter gourd peroxidase entrapped on calcium-alginate-starch beads was employed for the treatment of water, polluted with benzidine, in a batch process as well as in a continuous reactor. The immobilized enzyme had the same pH and temperature optima as the soluble enzyme. The immobilized enzyme could effectively remove more than 70% of benzidine in a stirred batch process after three hours. After its sixth repeated use, the immobilized enzyme was able to oxidatively degrade and polymerize 58% of benzidine. The horizontal bed reactor, containing the peroxidase entrapped on calcium-alginate-starch beads, retained more than 40% benzidine removal efficiency after one month of its continuous operation. The absorption spectra of the treated benzidine exhibited a marked difference in the absorption at various wavelengths, compared with untreated compound. The horizontal bed reactor containing immobilized peroxidase would be significantly successful for the large-scale treatment of water polluted with aromatic compounds